Green approach for fabrication of chitosan‐neem gum polyelectrolyte stabilized penta and hexagonal nanoparticles and in‐vitro cytotoxic potential toward breast cancer (MCF‐7) cells. Issue 2 (2nd November 2020) - Malviya, Rishabha
Abstract: The present investigation aimed to utilize chitosan‐neem gum polysaccharide (Ch‐NGP) polyelectrolyte complex for the fabrication of hexagonal and pentagonal nanoparticles using antisolvent precipitation method. Fabricated nanoparticles were found in the range of 63.1 to 447.2 nm with the entrapment efficiency of 76.80 ± 1.28 to 89.82 ± 2.32%. A nonlinear correlation between the independent variable and response was observed after the regression coefficient based linearity analysis. Drug release was carried out using the egg membrane and tomato membrane as a biological barrier. All the formulations show peculiar release pattern viz. initial immediate release, followed by sustained release and final burst release of the drug. Similarity factor analysis easily showed a significant difference in drug release patterns when the egg membrane and tomato membrane were utilized as biological barriers (S˂50). Anticancerous effect against breast cancer cells line (MCF‐7) shows better control over cell growth when etoricoxib loaded nanoparticles were used in place of pure etoricoxib. Particle size growth analysis elicits that significantly no "Ostwald ripening" was observed after 45 days. It can be concluded from the findings of the experiments that Ch‐NGP polyelectrolyte functionalized hexagonal and pentagonal nanoparticles can be utilized for passive targeting of tumor cells due to its unique properties. Abstract : Addition of kheri gum polysaccharide solution into chitosan solution results in the formation of polyelectrolyte stabilized pentagonal and hexagonal nanoparticles. Formulated nanoparticles of etoricoxib showed better control over the growth of human breast cancer cells line (MCF‐7) than non‐encapsulated etoricoxib.